EFFECT OF SAPPAN WOOD (Caesalpinia sappan L) EXTRACT ON BLOOD GLUCOSE LEVEL IN WHITE RATS - Saefudin, Saefudin; Pasaribu, Gunawan; Sofnie, Sofnie; Basri, Efrida (Secretariat of Forestry Research and Development Agency, 2014)
Sappan wood or kayu secang (Caesalpinia sappan L.) was reported of having medicinal properties, such as natural antioxidant, relieve vomiting of blood, and mix of ingredients for malaria drugs. The research was conducted to study the influence of ethanol extract from sappan wood on blood glucose level of white rats. The study of the blood glucose level in rats was carried out by using glucose tolerance method. It was measured by Refloluxs (Accutrend GC) with Chloropropamide 50 mg/200 g BW (Body weight) as positive control. The ethanol extracts were used in various concentrations 10, 20, 30, 40 and 50 mg/200 g BW per-oral and was observed every hour, beginning one hour before to 7 hours after the extract being administered. The results showed that treatment of ethanol extract of sappan wood by administer doses gave remarkable effect on the blood glucose level in white rat. It reduced the glucose level in the blood compared to the negative and positive control. Treatment of dose 30 mg/200 g BW gave similar effect to positive controls, while a dose of 50 mg/200 g BW gave lower blood glucose level (93 mg/dl) than the positive controls.